UPAYA PENINGKATAN HASIL BELAJAR KONSEP JARINGAN HEWAN MELALUI MEDIA FLASHCARDS PADA SISWA KELAS XI IPA MAN 2 PADANGSIDIMPUAN T. P. 2015/2016 - raisah surbakti (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
The purpose of this research is to know the increase of activity and learning result of animal network concept on the students of class XI IPA MAN 2 Padangsidimpuan through the use of flashcards media. This classroom action research is conducted with three cycles. The subjects were students of class XI IPA 5 MAN 2 Padangsdimpuan in the academic year 2015/2016 amounted to 25 students, which is 10 men and 15 women, and the biology teacher in charge of teaching in class XI IPA 5 MAN 2 Padangsdimpuan in the academic year 2015/2016. This research was conducted on 18 to 25 August 2016. Instrument in the form of observation sheet, test of learning result, analysis of qualitative and quantitative data. The indicator of success in accordance with the minimum completeness criteria (KKM) applied in MAN 2 Padangsidimpuan is the learning result of students at least 85% and the completeness of classical learning at least 85%, learning is said to be effective when 85% of students have been actively involved, whether mental, physical, mental, and social. Result of research: the cycle I average of process evaluation from student activity got 60,6%, mean of average result of learning result of animal tissue concept with new completeness reach 74%. In the cycle II of the average process assessment that is as much as 78.67% and the average assessment of learning outcomes is 86% complete. The average third cycle of process assessment is 96% and the average result is 96%. Implementation of learning in cycle III the average assessment of results has reached predetermined indicator that 85% of students achieve Minimization completeness Criteria (KKM) as much as 85%.